The changes of atrial complex on electrocardiogram in metabolic syndrome patients with cardiac arrhythmias - E. D. Dzhishambaev (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To study the parameters of P wave in metabolic syndrome (MS) patients and to evaluate their relation with cardiac rhythm disorders development.Material and methods. Totally, 203 men studied with MS and 16comparable by age men with arterial hypertension alone. All participants underwent 24-hour electrocardiogram monitoring (ECG), where the P wave length was measured, as Macruse index and length of negative P phase in lead V1. According to the presence of arrhythmia, patients were selected to groups: no arrhythmia, ventricular extrasistoly, supraventricular extrasystoly and atrial fibrillation.Results. In supraventricular extrasistoly group and in paroxysmal atrial fibrillation group all parameters of atrial ECG were significantly increased and were higher than the same parameters in control group, as in patients with ventricular extrasistoly or no arrhythmia.Conclusion. The increase of total P-wave duration and of negativephase in lead V1, as well as Macruse index is associated with increased prevalence of supraventricular rhythm disorders in MS.